Structure‐function relationships of starch components. Issue 1 (5th December 2014) - Vamadevan, Varatharajan; Bertoft, Eric; Tester, Richard F.
Abstract Starch continues to be an important renewable biopolymer in both the food and non‐food industries. Its properties, which vary depending on the plant source, stem directly from its structure. The recent substantial increase in knowledge of the molecular structure of starch components and the architecture of starch granules has contributed significantly to an enhanced understanding of the structural base of starch functionality. This résumé provides an overview of the present views of the starch structure‐function relationships with an emphasis on industrially important starch sources.